1970
DOI: 10.1071/ch9701117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and infrared spectra of some dithiocacodylate complexes

Abstract: The synthesis of dithiocacodylate complexes of the metals chromium(111), indium(111), manganese(11), cobalt(11), nicke1(11),� zinc(11), and copper(1) is described. The compounds can be prepared either from sodium dithiocacodylate Na[S2As(CH3)2] or by passing hydrogen sulphide through a methanolic solution of the metal cacodylate in the presence of hydrogen chloride. The infrared spectra in the region 4000-40 cm-1 of the new compounds have been recorded and assigned by a comparison with the spectra of several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…Bunsen found that the reaction of 2 with CuCl 2 and AuCl 3 gave the complexes Me 2 AsS 2 M [M¼Cu(I), Au(I)] and we and others confirmed the production of Cu(I) complex starting from 2 and from 7 [5,6].…”
Section: The Preparation Of Me 2 Ass 2 Tl From (2) and Tl(iii)supporting
confidence: 78%
See 4 more Smart Citations
“…Bunsen found that the reaction of 2 with CuCl 2 and AuCl 3 gave the complexes Me 2 AsS 2 M [M¼Cu(I), Au(I)] and we and others confirmed the production of Cu(I) complex starting from 2 and from 7 [5,6].…”
Section: The Preparation Of Me 2 Ass 2 Tl From (2) and Tl(iii)supporting
confidence: 78%
“…Although InCl 3 reacts with Me 2 AsS 2 Na Á 2H 2 O 7 to give (Me 2 AsS 2 ) 3 In, [6,7] InCl 3 simply binds to 2, Figure 2(i)-(vi). From the downfield shifting of the singlets, the dominant binding is on the As¼S sulfur.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations